Koszty produkcji i ceny żywca wieprzowego jako instrument przewagi konkurencyjnej - Stępień, Sebastian (Costs of Production and Prices of Pork as An Instrument of Competition Advantage, 2005)
Asking about the competitiveness of pork production in Poland we ask about the ability of the sector to keep or strengthen its position on the market. Currently the production of pork is the most important branch of agriculture in Poland. The number of pigs amounts to 12% of total number in the EU and the meat production constitutes above 9% of total meat production in the EU. Owing to this the potential of Polish agriculture is competitive for other member states, the more so because the production of meat in most of them exceeds the internal consumption. The aim of the paper is to analyse the procurement prices of pork and costs of raising pigs before and after the accession to the EU and to estimate the potential of Polish and EU states' agriculture, which will let us draw the conclusions about the competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 297-302